2009
DOI: 10.1055/s-0029-1210333
|View full text |Cite
|
Sign up to set email alerts
|

Is there a Relationship between Genetically Determined Haptoglobin Phenotype and Insulin-Dependent Diabetes Mellitus (IDDM)?1)

Abstract: The possible relationship between genetically determined haptoglobin phenotype and insulin-dependent diabetes (IDDM), circulating insulin antibodies and the occurrence of microangiopathy was studied in 144 IDDM. There were no differences regarding the distribution of Hp-phenotypes in 144 patients in comparison with a control population (n = 1726). Irrespective of the Hp-phenotype, the degree and severity of diabetic complications (retinopathy and/or nephropathy) significantly increased with the duration of dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…[2028] However two other studies by Ratzman et al (1984) and Koda et al (2002), which compared diabetic patients with and without DR and found no difference in Hp phenotype distribution in two groups. [3233] The reasons for these discrepancies may be due to differences in type of diabetes, ethnic groups and other genetic contributors and also the collected data is relatively small.…”
Section: Discussionmentioning
confidence: 99%
“…[2028] However two other studies by Ratzman et al (1984) and Koda et al (2002), which compared diabetic patients with and without DR and found no difference in Hp phenotype distribution in two groups. [3233] The reasons for these discrepancies may be due to differences in type of diabetes, ethnic groups and other genetic contributors and also the collected data is relatively small.…”
Section: Discussionmentioning
confidence: 99%